Aerospace Power Development in India and Implications for Pakistan - Ameer Hamza Rana (BTTN Journal, 2023)
This paper evaluates the trends of aerospace military power development strictly in the India-Pakistan conflict setting. It analyzes the combat potential of aerospace technologies and explores how they add to the net war-fighting strengths of the respective India and Pakistan militaries. The primary question is to identity the gap in aerospace domain between India and Pakistan while making recommendations for Pakistan. The study finds serious efforts of aerospace military power development by India which challenges the military security of Pakistan. Pakistan has the leverage in employing drones for multiple roles against India but their potential remains limited due to minimal space infrastructure for navigation and communication.  The study uses the comparative method to analyze the profiles of India and Pakistan for aerospace development trends and to assess the emerging threats for Pakistan. It further enables us to foresee the evolving nature of future conflicts because aerospace technologies are likely to remain at the core of possible war in future.